2017
DOI: 10.1093/mmy/myx115
|View full text |Cite
|
Sign up to set email alerts
|

Identification of clinical isolates of Aspergillus, including cryptic species, by matrix assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS).

Abstract: An expanded library of matrix assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS) has been constructed using the spectra generated from 42 clinical isolates and 11 reference strains, including 23 different species from 8 sections (16 cryptic plus 7 noncryptic species). Out of a total of 379 strains of Aspergillus isolated from clinical samples, 179 strains were selected to be identified by sequencing of beta-tubulin or calmodulin genes. Protein spectra of 53 strains, cultured i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 29 publications
1
28
0
4
Order By: Relevance
“…According to MALDI‐TOF MS results, only 18 of 200 isolates identified by sequencing were confirmed as A flavus based on the Bruker score database (log‐score ≥2.0). According to our review of previous studies published since 2011 (Table ), MALDI‐TOF MS scores of ≥ 2.0 were reported as a reliable marker to be used in discrimination of Aspergillus species with the rate ranging from 30.2% to 100% . At the same time, it was indicated that the potential of MALDI‐TOF MS in the identification of cryptic and closely related species in different sections of the Aspergillus genus remained uncertain …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to MALDI‐TOF MS results, only 18 of 200 isolates identified by sequencing were confirmed as A flavus based on the Bruker score database (log‐score ≥2.0). According to our review of previous studies published since 2011 (Table ), MALDI‐TOF MS scores of ≥ 2.0 were reported as a reliable marker to be used in discrimination of Aspergillus species with the rate ranging from 30.2% to 100% . At the same time, it was indicated that the potential of MALDI‐TOF MS in the identification of cryptic and closely related species in different sections of the Aspergillus genus remained uncertain …”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that MALDI‐TOF MS is a promising approach to rapid and accurate identification of different clinically relevant pathogens, which was also successfully applied to discriminate among Aspergillus species . In the current study, we analysed the potential of MALDI‐TOF MS to discriminate between A flavus and A oryzae using a set of 121 clinical and 79 environmental A flavus isolates a priori identified as such by sequencing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Matrixassisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS) technique may be used in the identification of Aspergillus spp. and is a promising tool, particularly for the identification of rare species of Aspergillus [90,91]. This method allows a rapid and reliable identification of the isolate and therefore, an early start of effective antifungal therapy.…”
Section: Direct Microscopic Examination Culture and Identification Ofmentioning
confidence: 99%
“…İyonlar kütleleriyle orantılı hız kazanarak detektöre farklı zamanda çarpmaları ile kaydedilen sinyaller proteinlerin kütle spektrumlarını oluşturur. Görüntülenen spektrum, mevcut veri tabanındaki spektrumlarla karşılaştırılarak, hem cins hem de tür bazında tanımlama yapılır 9,10,11,12 .…”
Section: Maldi-tofunclassified